Inpatient hyperglycaemia improvement quality program. Issue 4 (22nd January 2014) - Bar‐Dayan, Y.; Landau, Z.; Boaz, M.; Chaimy, T.; Matas, Z.; Wainstein, J.
Summary Background Poorly controlled hyperglycaemia is associated with increased morbidity and mortality in hospitalised patients. Based on the view that hospitalisation provides a window of opportunity to improve patient quality of care and health status, a comprehensive program for treating hospitalised diabetic patients was initiated. This study assessed the effectiveness of the Inpatient Hyperglycaemia Improvement Quality Program (IHIQP) over a 4‐year period. Methods Pre‐test post‐test design. In the pre‐intervention period (August–December 2007), an institution‐wide blood glucose monitoring system was introduced in August 2007. The remaining program components were introduced in January 2008, including implementing a hospital care protocol based on the 2007 American Diabetes Association Standards, a multidisciplinary team that participates in patient care and arranges continuing care after discharge and comprehensive patient education prior to discharge. Program results from January 2008 through October 2011 were evaluated. Results During follow‐up, more than 600, 000 blood glucose tests were performed. Blood glucose values declined from 196.4 ± 98.4 mg/dl pre‐IHIQP (August–December 2007) to 174.5 ± 82.0 mg/dl post‐IHIQP (January–October 2011) (p < 0.0001). Prevalence of glucose values lower than 60 mg/dl declined from 2% to 1.3% (p < 0.004). Prevalence of glucose values ≥ 300 mg/dl declined from 13.6% to 8.4% (p < 0.0001). Concomitantly, the proportion of in‐target values of 80–180 mg/dl increased from 47.7% to 58.1% (p < 0.0001). Conclusion This in‐patient hyperglycaemia quality improvement program led to improvements in‐patient glycaemic control, which continued over time. The effect of this improvement on in‐patient mortality and morbidity needs additional follow‐up.